Implementasi Sistem Hidroponik Ramah Lingkungan Menggunakan Galon dan Botol Bekas untuk Peningkatan Produksi Tanaman Sayur di Desa Balongwono - Nur Mila Eka Zaliyanty; Ivan Ardiansyah; Ananda Asa Firstha Affandi; Hendra Maulana (Jurnal Kabar Masyarakat, 2024)
In 2023, Indonesia generated 32.035 million tons of waste per year, with 49.6% coming from household waste (SIPSN, 2023). Balongwono Village in Mojokerto Regency, East Java, also faces waste problems and is an agricultural area with the majority of the population working as farmers. Vegetable production in this village is often suboptimal due to limited land and conventional farming methods. To overcome this problem, a socialization on the benefits and basic techniques of hydroponics was conducted, training on making hydroponic installations from used items, and mentoring to ensure the success of the system. The hydroponic system that utilizes used gallons and bottles as growing media aims to increase vegetable production in Balongwono Village. The results show that plants such as kale and pakcoy grow faster and fresher than conventional methods. In addition to increasing yields, this system also reduces plastic waste and lowers production costs. The implementation of this hydroponic method provides double benefits: increasing vegetable production and reducing waste. This method can be a reference for other villages with similar problems, contributing to environmental sustainability at large.